2017
DOI: 10.14507/epaa.25.2395
|View full text |Cite
|
Sign up to set email alerts
|

English language learner teacher effectiveness and the Common Core

Abstract: Common Core State Standards (CCSS) and teacher effectiveness are among the most contentious issues in education today. With an increase in English language learners (ELLs) and the rigorous requirements imposed by the CCSS, teachers are left unprepared and ELLs struggle to stay afloat. Using California as a case study, this research synthesis outlines the current problem, which includes the complexity of the CCSS, the achievement gap between ELLs and their peers, and ill-equipped teachers. In addition, present-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The percentage of students identified as English language learners 1 enrolled in schools has been steadily increasing in the United States (National Center for Education Statistics, 2019; Office of English Language Acquisition, 2020). As these numbers grow, teachers find themselves underprepared to meet the needs of their culturally and linguistically diverse learners while simultaneously attending to stringent federal and state policies (Barros et al, 2020; Johnson and Wells, 2017; Viesca et al, 2016).…”
Section: Literature Review: Surveying the Watersmentioning
confidence: 99%
“…The percentage of students identified as English language learners 1 enrolled in schools has been steadily increasing in the United States (National Center for Education Statistics, 2019; Office of English Language Acquisition, 2020). As these numbers grow, teachers find themselves underprepared to meet the needs of their culturally and linguistically diverse learners while simultaneously attending to stringent federal and state policies (Barros et al, 2020; Johnson and Wells, 2017; Viesca et al, 2016).…”
Section: Literature Review: Surveying the Watersmentioning
confidence: 99%
“…Results revealed that highly instructional practice had the most direct impact on student achievement. More studies as (Baker et al 2014;Bunch, 2014;Brown , 2019;Gándara and Santibañez, 2016;Johnson and Wells, 2017;Li Nan, 2013;Trickett et al 2012;van Lier & Walqui, 2012) proved that teachers needed quality skills, training, or professional development to teach ELL students. Thus the need for skillful and experienced teachers that could cope with the demands of the 21 st century is very important for the reform of any educational institution.…”
Section: Introductionmentioning
confidence: 99%
“…Teacher effectiveness contributes greatly to students' achievement and helps raise a school's academic performance and standards. Given its importance, many researchers are interested in studying teacher effectiveness with the aim of improving the performance of students and schools, specifically in critical subjects such as science and mathematics (Goe, Bell & Little, 2008;Habib, 2017;Johnson & Wells, 2017;Marulcu & Bozkus, 2017;Owoh, 2016;Robinson & Lewis, 2017).…”
Section: Introductionmentioning
confidence: 99%